The Impact of Fireworks on Selected Ambient Particulate Metal Concentrations Associated with the Independence Day Holiday - Danielle Rocco; Esther Morales; Tyler Deflin; Jason Truong; Jaebin Ju; Daniel B. Curtis (Atmosphere)
Fireworks are often used in celebrations and are a known transient source of extreme particulate air pollution, and the particles produced by fireworks are known to contain potentially harmful heavy metals. This study investigated ambient particulate metal concentrations associated with heavy firework use during the United States Independence Day holiday in July 2020 and July 2021 in Fullerton, California, located within the greater Los Angeles metropolitan area. For this study, barium (Ba), chromium (Cr), copper (Cu), lead (Pb), and strontium (Sr) were quantified, with Ba, Cu, and Sr being known tracers for fireworks and Cr and Pb being potentially harmful. Total suspended particulates (TSP) were collected with filters and then extracted and analyzed by graphite furnace atomic absorption spectroscopy. Hourly ambient particulate concentrations at a nearby monitoring station exceeded 500 μg m−3 and 300 μg m−3 in 2020 and 2021, respectively. Greater concentrations of overall particulate matter and ambient metal concentrations were observed during 2020 when compared to 2021, consistent with studies in the literature that have shown increased firework use in the area, likely due to the COVID-19 restrictions in place in 2020. In 2021, the Ba, Cu, and Sr concentrations peaked overnight on 4–5 July as expected, but the Cr and Pb concentrations peaked in the afternoon on July 5. In 2020, the peak concentrations of Cr and Pb were 510 ± 40 ng m−3 and 710 ± 30 ng m−3, respectively, while 4900 ± 200 ng m−3, 3860 ± 40 ng m−3, and 1810 ± 30 ng m−3 were observed for Ba, Cu, and Sr, respectively, among the highest ever observed to our knowledge.